Photo-Switching of Protein Dynamical Collectivity - M. Xu; D. George; R. Jimenez; A. Markelz (Photonics, 2021)
We examine changes in the picosecond structural dynamics with irreversible photobleaching of red fluorescent proteins (RFP) mCherry, mOrange2 and TagRFP-T. Measurements of the protein dynamical transition using terahertz time-domain spectroscopy show in all cases an increase in the turn-on temperature in the bleached state. The result is surprising given that there is little change in the protein surface, and thus, the solvent dynamics held responsible for the transition should not change. A spectral analysis of the measurements guided by quasiharmonic calculations of the protein absorbance reveals that indeed the solvent dynamical turn-on temperature is independent of the thermal stability/photostate however the protein dynamical turn-on temperature shifts to higher temperatures. This is the first demonstration of switching the protein dynamical turn-on temperature with protein functional state. The observed shift in protein dynamical turn-on temperature relative to the solvent indicates an increase in the required mobile waters necessary for the protein picosecond motions, that is, these motions are more collective. Melting-point measurements reveal that the photobleached state is more thermally stable, and structural analysis of related RFP’s shows that there is an increase in internal water channels as well as a more uniform atomic root mean squared displacement. These observations are consistent with previous suggestions that water channels form with extended light excitation providing O2 access to the chromophore and subsequent fluorescence loss. We report that these same channels increase internal coupling enhancing thermal stability and collectivity of the picosecond protein motions. The terahertz spectroscopic characterization of the protein and solvent dynamical onsets can be applied generally to measure changes in collectivity of protein motions.

Photo Switching of Protein Dynamical Collectivity - Xu, M.; George, D. K.; Jimenez, R.; Markelz, A. G. (arXiv:1906.00893, 2019)

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Probing the Stability of Fluorescent Proteins by Terahertz Spectroscopy - Xu, M. Y.; George, D. K.; Jimenez, R.; Markelz, A. G. (2014 39th International Conference on Infrared, Millimeter, and Terahertz Waves, 2014)
The higher transmission through tissues of long wavelength light motivates the development of fluorescent proteins with excitation shifted to the red. However red fluorescent proteins (RFPs) are more susceptible to photobleaching than their shorter wavelength counterparts. In particular RFPs are more susceptible to photobleaching [1]. A possible reason for this is a decrease in the structural stability of the beta barrel. Measurements of structural stability include atomic root mean squared displacement <x(2)> measured by the X-ray B-factor and neutron quasi elastic scattering. To date, X-ray measurements of RFP's do not indicate a structural stability change and systematic scattering studies have not been performed. Using THz dielectric response we examine if the picosecond structural flexibility decreases with increasing FP stability.
Keywords: dynamics

Terahertz transmission characteristics of high-mobility GaAs and InAs two-dimensional-electron-gas systems - Kabir, N. A.; Yoon, Y.; Knab, J. R.; Chen, J. Y.; Markelz, A. G.; Reno, J. L.; Sadofyev, Y.; Johnson, S.; Zhang, Y. H.; Bird, J. P. (Applied Physics Letters, 2006)
Frequency-dependent complex conductivity of high-mobility GaAs and InAs two-dimensional-electron-gas (2DEG) systems is studied by terahertz time domain spectroscopy. Determining the momentum relaxation time from a Drude model, the authors find a lower value than that from dc measurements, particularly at high frequencies/low temperatures. These deviations are consistent with the ratio tau(t)/tau(q,) where tau(q) is the full scattering time. This suggests that small-angle scattering leads to weaker heating of 2DEGs at low temperatures than expected from dc mobilit9y. (c) 2006 American Institute of Physics.
Keywords: field-effect transistors; photoconductivity; Physics; plasma-waves; radiation; resonant detection; subterahertz